The organized debate as a didactic method of civic education in the context of teacher education (Pedagogical Horizons, 2025)
This article examines organized debates as a didactic method that promotes democracy in the context of teacher education. In view of a changing communication culture and frontal teaching methods that are characterized by a lack of dialogue, the ability to engage in constructive dialogue is highlighted here as a key democratic competence. Organized debates offer a structured opportunity to discuss controversial topics, change perspectives and experience a democratic culture of discussion. Didactically, debates promote opinion building as well as the handling of controversy. The phases of an organized debate are illustrated using a selected debate from a seminar on democracy education at [location]. The reflection of the debate reveals both its potential (e.g. controversy, participation, conflict resolution skills) and its limitations (e.g. stress, language barriers, knock-out arguments). The structured distribution of roles and clearly structured timing enable learners to engage intensively with democratic principles. Overall, the organized debate is an effective methodology for democracy education that should be used more widely, particularly in teacher education, in order to contribute to a dialogue-oriented school culture in the long term.
Keywords: dialogue; debate; civic education; teacher education; higher education didactics